2022
DOI: 10.1080/27694127.2022.2042054
|View full text |Cite
|
Sign up to set email alerts
|

The ATG5 interactome links clathrin-mediated vesicular trafficking with the autophagosome assembly machinery

Abstract: Autophagosome formation involves the sequential actions of conserved ATG proteins to coordinate the lipidation of the ubiquitin-like modifier Atg8-family proteins at the nascent phagophore membrane. Although the molecular steps driving this process are well understood, the source of membranes for the expanding phagophore and their mode of delivery are only now beginning to be revealed. Here, we have used quantitative SILAC-based proteomics to identify proteins that associate with the ATG12–ATG5 conjugate, a cr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 77 publications
1
10
0
Order By: Relevance
“…Our model hypothesizes that ATG5 engages specific forms of BST2 tethered to virions to an LC3C-associated pathway, in which endosomal structures are customized by some ATG proteins. Interestingly, recent proteomic approaches described a strong link between ATG5 and clathrin adaptor protein complexes (AP)-dependent endocytic pathway ( 41 ). Moreover, several studies reported that Vpu/BST2 complex can interact with the AP complexes and that these interactions are important for BST2 antagonism by Vpu ( 11 ).…”
Section: Discussionmentioning
confidence: 99%
“…Our model hypothesizes that ATG5 engages specific forms of BST2 tethered to virions to an LC3C-associated pathway, in which endosomal structures are customized by some ATG proteins. Interestingly, recent proteomic approaches described a strong link between ATG5 and clathrin adaptor protein complexes (AP)-dependent endocytic pathway ( 41 ). Moreover, several studies reported that Vpu/BST2 complex can interact with the AP complexes and that these interactions are important for BST2 antagonism by Vpu ( 11 ).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, recent proteomic approaches described strong link between ATG5 and clathrin adaptor protein complexes (AP)-dependent endocytic pathway (41). Moreover, several studies reported that Vpu/BST2 complex can interact with the AP complexes and that these interactions are important for BST2 antagonism by Vpu (11).…”
Section: Discussionmentioning
confidence: 99%
“…Our model hypothesizes that ATG5 engages specific forms of BST2 tethered to virions to an LC3C-associated pathway, in which endosomal structures are customized by some ATG proteins. Interestingly, recent proteomic approaches described strong link between ATG5 and clathrin adaptor protein complexes (AP)-dependent endocytic pathway (41). Moreover, several studies reported that Vpu/BST2 complex can interact with the AP complexes and that these interactions are important for BST2 antagonism by Vpu (11).…”
Section: Discussionmentioning
confidence: 99%
“…This complex is localized on the outer membrane surface of the preautophagosomal structure and is involved in the expansion of the preautophagosomal outer membrane. Impaired activation of ATG5 and ATG12 often leads to impaired cellular autophagy [33][34][35] . BCL2L1 is a well-known anti-apoptotic protein, and it has been shown that BCL2L1 can inhibit autophagy by binding to beclin1 protein, which regulates the assembly of phagosomal membranes during autophagy 36,37 .…”
Section: Discussionmentioning
confidence: 99%